Analisis Nilai Karakter Motif Flora Batik Ngawi Sebagai Muatan Pendidikan Seni Rupa - Windy Ariani; Esthi Mindrati; Retno Winarni; Anesa Surya (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aimed to describe the character values conveyed in batik, especially in the flora motifs of Ngawi batik. This research used descriptive qualitative method with a hermeneutic approach. The samples of this study were teak batik, melon motifs, rice motifs, and bamboo motifs. The four samples were taken through purposive sampling technique, because these motifs were the main motifs of Batik in Ngawi Regency. In addition, data collection techniques used observation, interviews, documentation, and literacy studies. The interview used in this study was free guided interview, so that data collection activities only used an interview guide that contained an outline of the things being asked. Data of the research obtained were analyzed using qualitative descriptive analysis techniques, which consisted of 3 stages, namely data reduction, data presentation, and drawing conclusions and verification. The results of this study showed that the four flora motifs have various character values that can be used as a means of building the character of students.